Διερεύνηση των επιδράσεων προτύπων οικολογικής και απότομης οδήγησης στα μεγέθη της κυκλοφοριακής ροής και στις εκπομπές ρύπων - Αδαμίδης, Φίλιππος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Πολιτικών Μηχανικών. Τομέας Μεταφορών και Συγκοινωνιακής Υποδομής, 2017)
The aim of this diploma thesis is to assess the impact of ecological and harsh acceleration and deceleration profiles on the main properties of traffic flow and on the emissions of air pollutants. In order to collect the essential driving data, a mobile phone application was used as part of a previous study. The resulting database contains a total of 4156 urban trips originating from 100 distinct drivers. The extraction of the acceleration and deceleration profiles was based on k-means clustering, which resulted in the separation of the database in three clusters using some of the included variables, whereas the traffic simulation was done using the SUMO microscopic simulation software. The investigation of the impacts was based on three different scenarios; the first one concerns traffic simulation on a non-signalised urban arterial, the second one a simulation on a signalised urban arterial and the third one the simulation of an urban network with real O/D data (Luxembourg SUMO Traffic). The results showed that driving harshly leads to an increase in emissions, whereas driving smoothly leads to a statistically significant reduction in the emissions of air pollutants. Therefore, drivers who endorse a smoother accelerating and decelerating behaviour contribute positively to the reduction of air pollution from passenger cars, which means that they perform eco-driving.